Simultaneous observations of ESF irregularities over Indian region using radar and GPS - Sripathi, S.; Bose, S.; Patra, A.K.; Pant, T. K.; Kakad, Bharati; Bhattacharyya, A. (My University, 2008)
In this paper, we present simultaneous observations of temporal and spatial variability of total electron content (TEC) and GPS amplitude scintillations on L1 frequency (1.575 GHz) during the time of equatorial spread F (ESF) while the MST radar (53 MHz) located at Gadanki (13.5° N, 79.2° E, Dip latitude 6.3° N), a low latitude station, made simultaneous observations. In particular, the latitudinal and longitudinal extent of TEC and L-band scintillations was studied in the Indian region for different types of ESF structures observed using the MST radar during the low solar activity period of 2004 and 2005. Simultaneous radar and GPS observations during severe ESF events in the pre-midnight hour reveal that significant GPS L band scintillations, depletions in TEC, and the double derivative of the TEC index (DROTI), which is a measure of fluctuations in TEC, obtained at low latitudes coincide with the appearance of radar echoes at Gadanki. As expected, when the irregularities reach higher altitudes as seen in the radar map during pre-midnight periods, strong scintillations on an L-band signal are observed at higher latitudes. Conversely, when radar echoes are confined to only lower altitudes, weak scintillations are found and their latitudinal extent is small. During magnetically quiet periods, we have recorded plume type radar echoes during a post-midnight period that is devoid of L-band scintillations. Using spectral slopes and cross-correlation index of the VHF scintillation observations, we suggest that these irregularities could be "dead" or "fossil" bubbles which are just drifting in from west. This scenario is consistent with the observations where suppression of pre-reversal enhancement (PRE) in the eastward electric field is indicated by ionosonde observations of the height of equatorial F layer and also occurrence of low spectral width in the radar observations relative to pre-midnight period. However, absence of L-band scintillations during post-midnight event, when radar observed plume like structures and scintillations were recorded on VHF band, raises questions about the process of evolution of the irregularities. A possible explanation is that whereas small scale (~3 m) irregularities are generated through secondary waves that grow on the walls of km scale size irregularities, in this case evolution of the Rayleigh-Taylor instability itself did not extend to irregularities of scale sizes of a few hundred meters that produce scintillation on a L-band signal.
Keywords: ESF irregularities; Equatorial ionosphere; Ionospheric irregularities; Radar; TEC index